Study of CO2 Adsorption on Chemically Modified Activated Carbon With Nitric Acid and Ammonium Aqueous - Giraldo, Liliana; Vargas, Diana Paola; Moreno-Piraján, Juan Carlos (Frontiers in Chemistry, 2020)
The increase in CO2 concentrations in the atmosphere in recent years, has evidenced the need to find technological alternatives to remove this pollutant from the environment. In this sense, adsorption has been positioned as a promising option for CO2 removal, using porous materials such as activated carbon. In order to contribute to the production of adsorbent solids for the capture of CO2, in this work an activated carbon was prepared using as a lignocellulosic precursor African palm stone (Elaeis guineensis) by chemical activation with CaCl2 and H3PO4. Additionally the material obtained was subjected to a chemical modification with HNO3 and NH4OH, in order to study the influence that these treatments have on the CO2 adsorption capacity of the prepared porous material. The carbonaceous materials were characterized by physical adsorption of N2 at 77K, CO2 at 273K, proximate analysis, Boehm titrations and immersion calorimetry in water and benzene. Activated carbons have a BET area between 634 m2g-1 and 865 m2g-1, with a micropore volume between 0.25 cm3g-1 and 0.34 cm3g-1. The experimental results indicated that the modification of activated carbon with HNO3 and NH4OH generates a decrease in the surface area and pore volume of the material, as well as an increase in surface groups that favor the adsorption of CO2, which was evidenced by an increase in the adsorption capacity of this gas.